BIMBINGAN REINFORCEMENT UNTUK MENINGKATKAN DISIPLIN BELAJAR PADA PESERTA DIDIK KELAS VII: SMP NEGERI 2 PAKEM BONDOWOSO - SUSANTI (Dewan Pendidikan Bondowoso, 2021)
This study aims to improve learning discipline and to find out optimally about the problems that occur in students which have an impact on decreasing enthusiasm for learning. The study was conducted for 2 cycles, involving 25 grade VIIC students of SMP Negeri 2 Pakem. The success indicator set is 85% of students with learning discipline. The data were obtained through classroom observation as the main data, and the distribution of questionnaires at the end of the cycle as data support. The results showed; before the application of the strengthening approach, only 60% of students were disciplined in learning, after the reinforcement guidance approach in cycle 1 reached 72%, a significant increase in learning discipline in cycle 2 reached 92% of active students according to the success criteria